2011
DOI: 10.1172/jci43615
|View full text |Cite
|
Sign up to set email alerts
|

Dual elimination of the glucagon and GLP-1 receptors in mice reveals plasticity in the incretin axis

Abstract: Disordered glucagon secretion contributes to the symptoms of diabetes, and reduced glucagon action is known to improve glucose homeostasis. In mice, genetic deletion of the glucagon receptor (Gcgr) results in increased levels of the insulinotropic hormone glucagon-like peptide 1 (GLP-1), which may contribute to the alterations in glucose homeostasis observed in Gcgr -/-mice. Here, we assessed the contribution of GLP-1 receptor (GLP-1R) signaling to the phenotype of Gcgr -/-mice by generating Gcgr -/-Glp1r -/-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 59 publications
(81 reference statements)
8
86
0
Order By: Relevance
“…However, the acute nature of the increase in circulating glucagon also suggests that partial blockade of the glucagon receptor is most likely driven by a direct systemic feedback loop but might also be impacted by decreased overall glucagon clearance. Studies in mice have provided conflicting results regarding the role of GLP-1 in the improved glucose metabolism observed in glucagon receptor knockouts (26,27). Our results suggest that GLP-1 is unlikely to contribute to the efficacy of LY2409021 because active hormone levels are unchanged.…”
Section: Discussionmentioning
confidence: 65%
“…However, the acute nature of the increase in circulating glucagon also suggests that partial blockade of the glucagon receptor is most likely driven by a direct systemic feedback loop but might also be impacted by decreased overall glucagon clearance. Studies in mice have provided conflicting results regarding the role of GLP-1 in the improved glucose metabolism observed in glucagon receptor knockouts (26,27). Our results suggest that GLP-1 is unlikely to contribute to the efficacy of LY2409021 because active hormone levels are unchanged.…”
Section: Discussionmentioning
confidence: 65%
“…The contribution of increased GLP-1 concentrations to the altered glucose tolerance in Gcgr -/-has been investigated in STZ-treated Gcgr -/-mice, and inhibition of GLP-1 action had no effect on glucose tolerance but eliminated the improvement found in the STZ-treated Gcgr -/-mice [19]. The double knockout mouse, Gcgr -/-Glp1r -/- [20] has normal random fed blood glucose levels and a normal i.p. glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that plasma levels of GLP-1 and GLP-2 were dramatically increased in GCGR Ϫ / Ϫ mice ( 32,33 ).…”
Section: Effects Of Gra On Cholesterol Absorption In Hgcgr Micementioning
confidence: 97%